2016
DOI: 10.1590/s1517-707620160003.0074
|View full text |Cite
|
Sign up to set email alerts
|

Painéis sanduíches de poliéster reforçado com fibras de rami para aplicação na Construção Civil

Abstract: RESUMONeste trabalho foram produzidos e caracterizados mecanicamente compósitos de resina de poliéster reforçada com tecido bidirecional de fios de rami, com diferentes teores de reforço. Estes compósitos foram testados experimentalmente e numericamente como faces de painéis sanduíches formados com núcleos de bucha vegetal impregnada com resina de poliéster e poliestireno expandido -EPS. A caracterização mecânica dos materiais em estudo foi realizada em laboratório a partir de ensaios de tração e flexão, e sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…Brazil is one of the greatest producers of the plant and it cultivates those fibers in Northeast hinterlands in semi-arid regions, for the facility of the plant to adapt itself to dry regions [17]. Sisal fibers present adequate mechanical properties to the production of CFRP with application in civil industry [18,19]. Its usage in the production of the composites with thermoplastic matrices [20,21] and thermoset [22,23] was extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is one of the greatest producers of the plant and it cultivates those fibers in Northeast hinterlands in semi-arid regions, for the facility of the plant to adapt itself to dry regions [17]. Sisal fibers present adequate mechanical properties to the production of CFRP with application in civil industry [18,19]. Its usage in the production of the composites with thermoplastic matrices [20,21] and thermoset [22,23] was extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that two types of failures occurred the panels with a bushing core, by detachment of the faces and by shear of the core. However, they claimed that they were excessive deformations in the test and that it would not happen under normal conditions of use [32]. Thus, according to the studies mentioned above, the addition of fibers in polymeric matrices proves to be an excellent alternative for reinforcement in composites, especially when combined with chemical compounds.…”
Section: Mechanical Properties Of the Bushing As Reinforcement In A M...mentioning
confidence: 99%
“…A combinação de materiais vegetais com termoplásticos é algo visto como grande potencialidade, no que tange critérios de sustentabilidade de novos materiais, algumas fibras já tiveram sua potencialidade evidenciada, como as fibras de coco, sisal, bagaço de cana-de-açúcar, cânhamo e algodão [14,15]. O presente artigo visa difundir o uso de resíduos vegetais como aditivos poliméricos em termoplástico.…”
Section: Figura 1: Fruto De Tucumã (Astrocaryum Aculeatum)unclassified